Assessment of Solid Polymer Electrolyte Films of PVA Doped with Different Compositions of Zinc Sulphide (ZnS) Systems - R. Venugopal; K. Sudhakar; N. Narsimlu; CH. Srinivas (Recent Developments in Chemistry and Biochemistry Research Vol. 4, 2024)
The present paper investigates solid polymer electrolyte films of PVA doped with different compositions of zinc sulphide (ZnS) systems. Polyvinyl alcohol (PVA) is well-known for its tremendous impact strength at low temperatures, especially its flexibility, good moldability, high strength, heat-stable and chemical resistance. Polyvinyl alcohol (PVA) based Zn2+ ion conducting solid polymer electrolyte was prepared using a solution-cast method. To study the structure, measurements were made using Fourier transform infrared analysis (FT-IR) and X-ray diffraction (XRD). To learn more about the material’s optical characteristics, the 200–800 nm range optical absorption spectra were examined. The material’s optical absorption edge, direct energy gap, and indirect energy gap were included in this data. The direct optical energy gap for pure PVA lies at 6.08 eV, while PVA doped with zinc sulphide ranges from 5.28 to 5.68 eV for the different compositions. It was evident that the energy gaps and band edge values transferred to lower energies on doping with ZnS up to a dopant concentration of 92 wt.% of PVA and 8 wt.% of ZnS. In order to learn more about the conductivity order and charge transport in these materials, the ionic conductivity and transference number of PVA polymer electrolytes were measured for this investigation. The charge transport in PVA polymer electrolyte was measured to be largely due to ions (tion=0.97), as indicated by the transference number. Increasing the ZnS concentration and the temperature were both found to raise the ionic conductivity. The discharge properties of solid-state battery cells made with this PVA polymer electrolyte were studied while operating under a constant load of 100 kW. The evaluated cell para- meters of the cell (Zn/92 PVA:08 ZnS)/(I2 + C + electrolyte)) offer a significant application for solid-state batteries. Hence, the analyzed properties of Zn2+ ions doped with PVA polymer electrolytes are highly acceptable and promising for battery applications.